Answer: y = (x + 1)*(x - 4)
Explanation:
The points of the equation are:
( -2 ,6), ( -1 0) , ( 0, -4) ( 1 ,-6) (2,-6) ( 4 ,0) and ( 5,6)
The first thing you can see is that the roots are:
( -1 0) and ( 4 ,0)
the roots are x1 = -1 and x2 = 4
and we know that we can write a polynomial as:
y = a*(x - x1)*(x - x2)
So our function can be:
y = a*(x - (-1))*(x - 4)
we also know that this graph passes trough the point (0, -4) so we can chek if this equation is correct:
y(0) = a*(0 + 1)*(0 - 4) = -4
a*1*-4 = -4
then y = (x + 1)*(x - 4)